2010
DOI: 10.1210/jc.2010-0061
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Growth Hormone Deficiency in Severe Fibromyalgia Syndromes

Abstract: FM patients show a high prevalence of GH axis dysfunction. A significant number of patients show biochemical patterns of GH deficiency as well as some degree of GH resistance and might be potential candidates for substitution treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…Other reports have also shown that GH treatment is an effective pain therapy for patients with fibromyalgia [3,4,9,10,31,34,42]. However the effect in fibromyalgia patients was mainly found in those with corresponding low IGF-1 levels.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Other reports have also shown that GH treatment is an effective pain therapy for patients with fibromyalgia [3,4,9,10,31,34,42]. However the effect in fibromyalgia patients was mainly found in those with corresponding low IGF-1 levels.…”
Section: Discussionmentioning
confidence: 95%
“…Similar to GH releasing molecules such as ghrelin or GHRH [10, 54], IGF-1 and its receptor IGFr1, have also been demonstrated to be involved in nociceptive processing [16,46] in adult rodents possibly by modulating neuronal excitability [74]. Interestingly, in mice overexpressing IGF-2, studies have found reduced sensory innervation of the skin, which may play a role in peripheral responsiveness [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reports have also shown that GH treatment is an effective pain therapy for patients with fibromyalgia [3,4,9,10,31,34,42]. However the effect in fibromyalgia patients was mainly found in those with corresponding low IGF-1 levels.…”
Section: Clinical Significancementioning
confidence: 95%
“…However, GH-related signaling molecules such as GH release hormone (GHRH) and ghrelin have been found to decrease mechanical and thermal hypersensitivity after inflammation [15,64] in adult rodents. In addition, recent human studies have showed that GH treatment provides analgesia in a subpopulation of adult patients with fibromyalgia [3,4,9,10,31,34,42].…”
Section: Introductionmentioning
confidence: 99%